PERANCANGAN REPOSITORY SEKOLAH DI PERPUSTAKAAN SMA NEGERI 5 MAGELANG - Suryanto Suryanto (Publication Library and Information Science, 2017)
Regulation of the Minister of State for Administrative Reform and Bureaucratic Reform No. 16 of 2009 on Functional Master and credit figures, Article 17 stipulates that for the promotion of teachers should make scientific publications and / or innovative work. Therefore, the existence of scientific papers or books work the teacher will always be growing every year. But the library space of SMA Negeri 5 Magelang that small would not be able to accommodate any paper in hardcopy. Then need other alternatives that can accommodate all these papers with not a lot of space is to create a school repository. To build a school repository required a benchmarking process began, preparing resources, leadership support, procedures and regulations, hardware and software as well as network and information management to handle local content. The results of research in the form of a model repository schools that applied by utilizing existing infrastructure at the Library of SMA Negeri 5 Magelang